The effect of financial innovation on bank profitability: assessing the role of country-level corporate governance in Asian countries / Hussain Abbas ... [et al.] - Abbas, Hussain; Guo, Fei; Rafique, Kalsoom; Abbas, Shah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Country-level corporate governance reduces uncertainty, transaction, and search costs and ultimately affects banking performance. In this study, we look at the connections between financial innovation and a bank’s ability to make money, as well as the role of corporate governance at the country level. We utilized the data of 88 banks from five South Asian countries over the period 2007–2019. In addition, we used the data from World Bank governance indicators for country-level governance. The results showed that there is a strong and positive link between financial innovations and a bank’s profits. This suggests that financial innovation makes banking services better and more efficient, which helps banks make more money. Also, corporate governance at the country level had a positive and important effect on the link between financial innovation and a bank’s profits.